(Jasminum officinale L.)(The Effect of fat types and the thickness of chassis on the enflourage process of jasmine oil (Jaminum officinile L.) - Endah Djubaedah; Achmad Moestafa; Edwin S. Permana; Rosalina Dewi s. (Warta Industri Hasil Pertanian, 2005)
Jasmine oil was not vapourable by steam destilation due to heat unstability and possibility of hydrolysis.Enfleuration process was recommended when jasmine oil is to be isolated from its flower.Vegetable and animals fat and the mixture of both of them in the form of shortening were studied as jasmine oil absorbent.Varieties of fat and the thickness of chassis effected the yield and the characteristic of jasmine oil were isolatedby this method.It was found that more the thicker the fat layer on chassis the higher oil content can be isolated.Three variables of fat thickness have been studied i.e. 0.5,0.8 and 1.1 cm.From the experiments it was found that the highest yield was obtained on 1.1 cm thicness i.e. 0.29 % from vegetable fat 0.40 % from animal fat and 0.56% from the mixture of animal and the vegetable fat.Based on the rendemen and ester value.The best treatment was animal fat with fat thickness of chassis about 1.1cm produced rendemen about 0.40% and ester value 158.01.